Pemberian Stimulasi Oleh Ibu Berhubungan dengan Perkembangan Anak Usia 1-3 Tahun di Wilayah Kerja Bidan Desa Kertaharja - Sofaniah Nurrahmi; Isfaizah, Isfaizah (Journal of Holistics and Health Science, 2021)
Toddler development is very important to note, the first five years of life are very sensitive to the environment and lasts very short and cannot be repeated. Globally each year more than 200 million children less than 5 years of age show developmental delays and 86% occur in developing countries. In child development, the role of parents, especially mothers, is one of the supporting factors in the suitability of child development. The stimulation given by parents to children will create children who are smart, can develop and grow optimally, are independent, have normal emotions and are easy to adapt. The purpose of this study was to determine whether there is a relationship between maternal stimulation with the development of children aged 1-3 years. This research method is an analytical observational study with a cross sectional approach. Population in this study were all mothers who have toddlers aged 1-3 years as many as 130 people and the study sample was 57 people who were taken by purposive sampling technique. This research was conducted in the work area of ​​Kertaharja village midwives in December 2020. The instrument used in this study was to use a maternal stimulation questionnaire and for child development using KPSP. Data analysis includes univariate analysis and bivariate analysis with chi square test with significant level <0.05. Univariate analysis showed that most of mothers provided good stimulation (75,4%) and children had normal development (64,9%). The results of the bivariate analysis showed that there was a significant relationship between the provision of maternal stimulation on the development of children aged 1-3 years in the Kertaharja Village Midwife Work Area with a p value of 0.001; p <(0.05). Maternal stimulation is very important for optimal development of children aged 1-3 years. It is recommended that parents be more active in providing stimulation to children according to the child's age ABSTRAK Lima tahun pertama kehidupan merupaka periode emas pertumbuan balita dan 86% kejadian keterlambatan perkembangan pada anak usia kurang dari 5 tahun terjadi di negara berkembang. Peran orang tua merupakan salah satu faktor pendukung dalam perkembangan anak. Stimulasi yang diberikan orangtua pada anak akan menciptakan anak yang pintar, mandiri, emosi yang normal dan tumbuh kembang dengan optimal. Tujuan penelitian ini adalah untuk mengetahui apakah ada hubungan antara pemberian stimulasi oleh ibu dengan perkembangan anak usia 1-3 tahun. Desain penelitian ini analitik observasional dengan pendekatan crossectional. Populasi adalah seluruh ibu yang memiliki balita usia 1-3 tahun di Desa Kertaharja sebanyak 130 orang dan sample sebanyak 57 orang diambil dengan teknik purposive sampling. Instrumen yang digunakan ialah kuesioner stimulasi ibu dan untuk perkembangan anak menggunakan KPSP. Analisis data meliputi analisa univariat dan analisis bivariat dengan uji chi square taraf signifikan <0,05. Analisis univariat sebagian besar ibu memberikan stimulasi yang baik pada anaknya (75,4%) dan anak memiliki perkembangan yang normal (64,9%). Analisis bivariat ada hubungan yang signifikan antara pemberian stimulasi oleh ibu terhadap perkembangan anak usia 1-3 tahun di Wilayah Kerja Bidan Desa Kertaharja (p= 0,001). Semakin baik pemberian stimulasi oleh ibu maka semakin bagus juga perkembangan yang dialami anak. Disarankan kepada orang tua yang masih kurang baik dalam menstimulasi anaknya untuk lebih aktif lagi dalam memberikan stimulasi kepada anak agar anak berkembang dengan optimal